RESEARCHES ON HIGHER EDUCATION INSTITUTION STUDENTS’ PERCEPTION OF ORGANIZATIONAL JUSTICE IN TURKEY: LITERATURE REVIEW - BAYAR, Yılmaz (SSD Journal, 2022)
In this study researches on organizational justice conducted for the students of higher education institutions in Turkey in last 17 years were analyzed by the literature review method. It is aimed to reveal the organizational justice perception of students from different aspects. Initially the concept of organizational justice and its components were explained. Subsequently, the information obtained by the literature review method was compiled. As a result of the study, it was seen that the organizational justice perception of the students of higher education institutions was medium level. It has been determined that the level of perception of distributive justice which is one of the organizational justice components is relatively high. Significant relations were found between organizational justice; organizational commitment, organizational silence, organizational citizenship behavior, organizational cynicism and job satisfaction. It has been revealed that organizational justice components show a significant distribution according to the demographic variables of students' faculty, department, class and gender. Higher education institution students’ positive perception of organizational justice can enable them to develop positive attitudes in general. These attitudes may increase organizational performance. For these reasons, students' positive perception of organizational justice can create beneficial organizational consequences for higher education institutions.